Participatory characterization of the Short-eared Somali goat and its production environment around Dire Dawa, Ethiopia - Gebreyesus, G.; Haile, Aynalem; Dessie, Tadelle (2012)
Characterization of the Short-eared Somali goat population around Dire Dawa, Ethiopia, was undertaken in a community-based and participatory approach. Range of participatory tools, including Focal Group Discussions, participatory mappings and transect walks, were employed to study the local community's Indigenous knowledge and practices in animal breeding. The breeding objective was defined in a participatory manner through own-flock ranking experiments. Physical description of the goat population was made based on the "key characteristics" concept used by the community to distinguish their goat type among other breeds within their migratory reach. The Issa community maintains a perception of special association towards the Short-eared Somali goat type, claiming a historic role in its development and adaptation. Local myths persistent in the community associate the origin of the Short-eared Somali goat breed with the communal ethno-history. The community generally practices selective pure breeding employing rather complex indigenous knowledge and traditional practices aimed at polishing the gene pool towards the dictates of the environment. Patchy color patterns were generally dominant (59.8%) in the goat population, while 34% of the patched goats had a unique pattern of black spots on the center core of the face and a black stripe across the spine. Goats were kept for multifaceted purposes ranging from products like milk and meat to functions in socio-cultural and financial state of affairs. The production system was characterized with lack of feed supplementation and rangelands provide the only source of feed throughout the year. Although the production environment was characterized with recurrent droughts and high prevalence of goat diseases, goats were found to have significant contributions to the livelihood of the Issa pastoralists in the study area.